The Tenth World Forestry Congress - 'Forests our future heritage' - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The Tenth World Forestry Congress will take place in Paris from 17 - 26 September, 1991, under the double aegis of the United Nations Food and Agriculture Organization (FAO) and the French government. Some 160 countries will be represented by 3000...